"Clearness of style, plainness of statement" Experiment Station Bulletins In The Early Years - Lynn B. Padgett (Journal of Applied Communications, 1987)
Experiment Station bulletins of the late 19th century were written by the scientists themselves in candid, colorful language. The early bulletins from one state (North Carolina) display the personalities of the writers and the excitement and frustration of developing the disciplines of the new agricultural sciences.